Effectiveness of psychoeducation interventions for pregnant women with gestational diabetes mellitus: an integrative review - Mutairah Alshammari; Regina Lai Tong Lee; Michelle Stubbs; Sally Wai-Chi Chan (BMC, 2024)
Abstract Background Gestational diabetes mellitus occurs in approximately 15-17% of pregnant women worldwide and causes high mortality and morbidity for mothers and infants. Pregnant women who are newly diagnosed with gestational diabetes mellitus experience higher levels of stress and anxiety than pregnant women without this condition. Thus, it is important to identify effective interventions to help pregnant women cope with the additional stress and anxiety associated with pregnancy-related complications. Aim This integrative review aimed to synthesise evidence on the effects of educational interventions for pregnant women with gestational diabetes mellitus regarding knowledge, self-efficacy, self-care behaviour, anxiety, depression, and birth outcomes. Methods An integrative review of articles published between 2009 and 2024, written in English and Arabic. The review followed the Whittemore and Knafl's 5-stage process framework. Results From the 922 abstracts identified using search terms, 16 articles were eligible for this review. Psychoeducational interventions were provided for (1) informational support: information about gestational diabetes mellitus, diabetes mellitus, blood glucose monitoring, exercise management, diet management, and stress; (2) motivational support: setting individual goals, enhancing health behaviours, and motivational messages; (3) emotional support: expression of feelings, enforcement of self-management, and sharing of experiences; and (4) relaxation techniques: breathing exercises, meditation, and mindfulness. In this review, only two studies entirely focused on reducing stress and anxiety through cognitive-behavioural stress management training and mindfulness training. The effects of the interventions on self-efficacy, knowledge, depression, anxiety, and birthing outcomes were inconsistent due to variations in intervention designs and duration. However, consistent positive outcomes were found in self-care behaviours. Conclusion This integrative review found informational and motivational support were frequently used by pregnant women. In contrast, emotional support and relaxation techniques were rarely used. Psychoeducational interventions may enhance self-care behaviours, improve self-efficacy, and reduce stress and depression for women with gestational diabetes mellitus. Nurses and midwives play an essential role in providing holistic care through comprehensive psychoeducational interventions for pregnant women.